Dragging motion of a two-link mobile manipulator with large pull force through singular configuration: theoretical analysis and experimental verification. (3rd June 2018) - Urakubo, Takateru; Kitagawa, Eri; Wan, Xianglong; Mashimo, Tomoaki
ABSTRACT: This paper reveals the advantageous feature of singular configuration for a two-link mobile manipulator by theoretical analysis, numerical simulations and experiments. When a mobile manipulator drags a heavy object on a flat floor, a large pull force is required to overcome the friction force between the object and the floor. In the motion obtained by numerical optimization, unlike humans, a two-link mobile manipulator pulls the object with a large force by passing through singular configuration. We analyze theoretically the force applied to the object by the manipulator under several assumptions, and show that a large pull force can be generated near singular configuration from the energy stored in the manipulator. The feasibility of the motion obtained by numerical optimization is also shown by experimental results. GRAPHICAL ABSTRACT: